2021
DOI: 10.1111/sapm.12444
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal patterns in a diffusive predator–prey system with nonlocal intraspecific prey competition

Abstract: We investigate the effect of nonlocal intraspecific prey competition on the spatiotemporal dynamics of a Holling-Tanner predator-prey model with diffusion. We first establish the criteria for Hopf, Turing, double-Hopf, and Turing-Hopf bifurcations, and determine the stable and unstable regions of the positive equilibrium. For Turing-Hopf bifurcation, by analyzing the normal form truncated to the third order, we derive that, with strong nonlocal interaction, the system exhibits the tristable phenomena, that is,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Some scholars have studied the predator-prey models with nonlocal competition. [21][22][23][24] Britton 25 and Furter and Grinfeld 26 introduced the nonlocal competition effect by modifying the u K as 1 K ∫ Ω G(x, 𝑦)u(𝑦, t)d𝑦, with some kernel function G(x, 𝑦). Chen and Yu 22 studied a diffusive predator-prey model with nonlocal competition effect, including stability of positive constant steady state and Hopf bifurcation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some scholars have studied the predator-prey models with nonlocal competition. [21][22][23][24] Britton 25 and Furter and Grinfeld 26 introduced the nonlocal competition effect by modifying the u K as 1 K ∫ Ω G(x, 𝑦)u(𝑦, t)d𝑦, with some kernel function G(x, 𝑦). Chen and Yu 22 studied a diffusive predator-prey model with nonlocal competition effect, including stability of positive constant steady state and Hopf bifurcation.…”
Section: Introductionmentioning
confidence: 99%
“…Since the resources is limited in nature, there is a competition within the population, and the competition is usually nonlocal. Some scholars have studied the predator–prey models with nonlocal competition 21–24 . Britton 25 and Furter and Grinfeld 26 introduced the nonlocal competition effect by modifying the uK$$ \frac{u}{K} $$ as 1KnormalΩGfalse(x,yfalse)ufalse(y,tfalse)dy$$ \frac{1}{K}{\int}_{\Omega}G\left(x,y\right)u\left(y,t\right) dy $$, with some kernel function Gfalse(x,yfalse)$$ G\left(x,y\right) $$.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [17], Wu and Song studied a diffusive predator-prey model with nonlocal effect and delay, and suggested that steady-state, Hopf, and steady-state Hopf bifurcations may occur. In [18], Geng et al studied Hopf, Turing, double-Hopf, and Turing-Hopf bifurcations of a diffusive predator-prey model with nonlocal competition. In [19][20][21][22], all the authors show that the nonlocal competition may induce stably spatially inhomogeneous bifurcating periodic solutions, which is different from the model without nonlocal competition.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the paper, N is the set of all positive integers, and N 0 = N∪{0}. As for the definitions of the mode-k 1 Turing bifurcation and mode-(k 1 , k 1 + 1) Turing-Turing bifurcation, as well as mode-k 2 Hopf bifurcation, mode-(k 1 , k 2 ) Turing-Hopf bifurcation, mode-(k 2 , k2 ) Hopf-Hopf bifurcation and so on, which will be mentioned later, the reader may refer to [7,13,19].…”
Section: Introductionmentioning
confidence: 99%